ACTIVE SHARING KNOWLEDGE UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN GURU- GURU MATEMATIKA SMA/SMK BINAAN MELALUI PENDAMPINGAN DI KULON PROGO - Giyarsih, Giyarsih (Jurnal Ilmiah Pendidikan Matematika (JIPM), 2016)
This research is meant to explain the problem solving efford which is found in academic supervision toward teachers of Mathematics in some guided schools, explains the problem solving steps by the supervisor in guided schools, and shows the teaching quality improvement by the Mathematics teachers in those guded schools. This research was done to some guded schools where ten Mathematics teachers of Senior High Schools or Vocational High School in Kulon Progo District are the subject. The strategy for improving the quality of Mathematics teaching application is through treatment of companion teaching in active sharing knowledge for instance through planning, the step of treatment in the teaching, teaching procedures and class management. The result of acompaniying the teachers of Mathematics shows that Mathematics teachers in Kulon Progo Distric still need some guidance from the supervisors especially in term of innovative teaching process, where most teachers lack of motivation, the Active Sharing Knowledge method can improve the activism of the teachers through out the whole teaching activities, improve the quality of teaching process, studentsâ activism, concept mastery and teacherâs skills in teaching process as can be seen as followed: the teaching quality of Mathematics teachers using Active Sharing Knowledge is 5%, studentâs participations is 46%, while teachersâ mastery of the concept is 14%, and positive reflection as a result of Mathematics Teachers guided teaching implementation using Active Sharing Knowledge where 84% stated agree and totally agree.Â Tujuan Penelitian ini adalah menjelaskan upaya pemecahan masalah yang ditemukan dalam supervisi akademik terhadap guru-guru Matematika disekolah binaan, menjelaskan langkah-langkah pemecahan masalah yang ditempuh pengawasÂ  disekolah binaan, dan menunjukkan peningkatan kualitas pembelajaran guru-guru Matematika di sekolah Binaan. Penelitian ini dilaksanakan pada sekolah binaan dengan objek Guru-Guru Matematika SMA/SMK di Kabupaten Kulon Progo sejumlah sepuluh orang guru Matematika. Strategi peningkatan kualitas pelaksanaan pembelajaranÂ  Matematika adalah melalui treathment pendampingan pembelajaran Active Sharing Knowledge antara lain tahap perencanaan, tahap treatmen pembelajaranÂ  Active Sharing Knowledge, prosedur pembelajaran Active Sharing Knowledge, dan pengelolaan kelas. Hasil pendampingan terhadap sepuluh orang guru matematika binaan, penulis menyimpulkan bahwa Guru-guru matematika di Kabupaten Kulon Progo ternyata masih sangat memerlukan pendampingan dari pengawas khususnya mengenai pelaksanaan proses pembelajaran inovatif, masih perlu adanya motivasi pengawas terhadap guru matematika, metode Active Sharing Knowledge dapat mengoptimalkan keaktifan guru dan siswa dari awal hingga akhir pembelajaran, meningkatkan kualitas proses pembelajaran, aktivitas siswa, penguasaan konsep, dan keterampilan guru dalam proses pembelajaran. Adapun besaran peningkatan tersebut sebagai berikut ini. Kualitas pembelajaran guru-guru Matematika denganÂ  Active Sharing Knowledge sebesar 5%. Besarnya peningkatan keaktifan siswa mencapai 46%, sedangkanÂ  peningkatan penguasaan konsep Matematika mencapai 14%. Diperoleh refleksi positif dari hasil pendampingan pelaksanaan pembelajaran guru-guru Matematika dengan Active Sharing Knowledge sebesar 84% menyatakan setuju dan sangat setuju.Â